Fast transient simulation of fernandez surge arrester model on a transmission line using ATP - Zolkhifly, Mohd Azfitry (2015)
Lightning is a very impressive phenomenon that occurs in nature. The amount of energy contained in a lightning stroke is very high and it can be extremely destructive. Electric distribution networks are particularly vulnerable to lightning strokes. A single stroke to a distribution line can be sufficient to cause a blackout throughout a feeder. To prevent this, power systems are protected with lightning rods, ground wires and surge arresters. This project purpose is to study and analysis the effect of lightning and surge arrester in power distribution system. Lightning surge is modeled using equation and will be use to analyze its effect to system. When fast front transients, such as from lightning, are to be investigated, the MOV surge arrester behavior representation is significantly different. So, fast front surge arrester is designed because it has dynamic characteristics that are significant for overvoltage coordination studies involving fast front surges. In order to investigate the effects of lightning and surge arrester in power distribution system, in this project Fernandez Surge Arrester is modeled. System simulation, using Alternative Transient Program (ATP) simulation software has been carried out. Simulation results have illustrated the output waveform of lightning surge, the model of fast front surge arrester and the effects of lightning and surge arrester in test 132kV system.